The influence of leadership and motivation work to discipline work teachers in high school - Sarkol, Yohana; Fitria, Happy; Missriani, Missriani (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to 1 to test the leadership of  1 ) teachers work discipline , 2 ) influence motivation teachers tenure to teachers work discipline , and 3 ) influence leadership and motivation of teachers work in togher teachers work discipline. This study using quantitative methods derived from sources both primary and secondary. Population and a working and motivation of teachers work discipline .The study is done in high school patra independent 01 Palembang .The collection of data using the survey with samples from 36 teachers. The data that has been collected analyzed using descriptive analysis and analysis of multiple regression. The result showed that : (1) is significant influence among schools to head leadership style discipline teacher in high school patra independent 01 Palembang; (2) any impact of the significant work to discipline the teacher in high school patra independent 01 palembang; (3)  Significant influence is of a style of leadership